Where we come from, where we go - Describing population change in New Zealand - Keith McLeod (New Zealand Government, The Treasury, 2018)
This paper describes new sub-national New Zealand population measures that have been developed by The Treasury using integrated administrative data. The paper accompanies the release of interactive online tools that present new data about the changing population of New Zealand and its territorial authority (TA) areas. The Insights Population explorer and Population directions tools can be accessed at https://insights.apps.treasury.govt.nz/. The paper provides a technical description of the construction of the data that underpins the tool, a comparison of the data against other sources of similar data, and some high level findings.
Keywords: 330